Impact of a Focused Nutrition Educational Intervention Coupled With Improved Access to Fresh Produce on Purchasing Behavior and Consumption of Fruits and Vegetables in Overweight Patients With Diabetes Mellitus. (January 2014) - Weinstein, Eleanor; Galindo, Rodolfo J.; Fried, Martin; Rucker, Lisa; Davis, Nichola J.
Purpose: The purpose of this study was to test the impact of distributing coupons redeemable at farmers markets plus an educational intervention on fruit and vegetable (F&V) purchase and consumption in overweight patients with type 2 diabetes (T2DM). Methods: Seventy-eight participants with T2DM being followed at Jacobi Medical Center, a large public hospital in the Bronx, New York, were randomized to receive the standard of care or a 1-hour session focused on benefits of F&V consumption and 6 in coupons. Questionnaires assessed demographics, F&V intake, and farmers market purchasing at baseline and 12 weeks. Clinical parameters were obtained through chart review at baseline and at 12 weeks. Results: Participants were predominantly Latino, females, and low income. At 12 weeks, there was a statistically significant increase in the number of participants in the intervention arm who reported purchasing from a farmers market. In addition, there was a minimal increase in fresh fruit intake in the intervention arm at 12 weeks. Conclusion: Focused education combined with a small economic incentive resulted in an increase in purchasing behavior and fresh fruit intake per day. A more intense behavioral intervention combined with increased access may result in a significant impact on obesity and diabetes, particularly among low-income and racially diverse communities.